The Local Wisdom on Sasak Tribe Sade Hamlet Central Lombok Regency - Widisono, Adrian (University of Merdeka Malang, 2019)
Traditional settlements that still survive until now one of them is in Sade Hamlet, Central Lombok Regency, NTB. This settlement is now a tourist destination because of the original architectural form of outer and inner spaces. These settlements have distinctive characteristics formed by local people from the time of their ancestors. Local wisdom is seen at the macro and micro scale which is a characteristic that has an opportunity value. This value arises due to trust (watu telu and watu lima) and culture (the use of cow dung when mopping) and moral values handed down by their ancestors. This study aims to explore local wisdom in settlements inherited from their ancestors from a macro and micro scale. To find out local wisdom at the macro and micro scale, a descriptive qualitative method was used with a research paradigm with literature review. The results of this study found local wisdom from a macro and micro scale. From a macro scale there are local wisdom in the form of home orientation, locations in the hills, structuring residential patterns, marariq (eloping) and weaving. On the micro scale there are local wisdom in the form of building elements in the form of roofs, doors, and also inner space, there is a belief held in the mass of ancestors in the form of watu telu and watu lima in the present mass.Â DOI: https://doi.org/10.26905/lw.v11i1.2711 Â